Water Hackathon : Lessons Learned - World Bank (Washington, DC, 2014)
The global revolution in low cost information and communication technologies can help address some of the developing world's oldest challenges in water and sanitation. More people today have access to a mobile phone than to a toilet. Convergence of widespread mobile phone ownership with new mobile commerce and location aware services offer new platforms for reach, transparency and participation in achieving water security. Water Hackathon had four interim objectives: (i) creation of a network of atypical partners engaged in finding solutions to water-related challenges, (ii) preparation of a list of challenges facing the water sector, (iii) development of new applications designed to address these challenges, and (iv) adoption of new applications and codes in World Bank projects. The openness of the approach attracted considerable attention from within the water community and also from print and online media, including blogs and social networks, which traditionally do not feature water content. 'This was the new Egypt at work,' said one participant in Cairo. Water Hackathon offered a low-cost, high-reward opportunity to open up water sector challenges to the talent and creativity of the ICT design and development community. This approach also required a change in mindset for the World Bank, calling for greater openness, experimentation and tolerance of failure.